ASSESSMENT OF POSTOPERATIVE ANALGESIC EFFECT OF RECTUS SHEATH BLOCK IN GYNECOLOGICAL LAPROSCOPIC SURGERY - Sobia Irum; Samina Saleem; Alia Bano; Sadia Irum; Kaneez Fatima (Journal of Ayub Medical College Abbottabad, 2024)
Background: Gynecological laparoscopic surgery is a minimally invasive surgical technique that can cause pain and discomfort in the postoperative period. To manage this pain, various analgesic techniques have been employed, including rectus sheath block (RSB). Bupivacaine is a long-acting local anesthetic that has been used in bilateral rectus sheath block (BRSB) for postoperative pain relief after laparoscopic surgery. The objective of this study is to assess the impact of bupivacaine’s bilateral rectus sheath block (BRSB) on post-laparoscopic pain relief with its intraperitoneal (IP) administration. Methods: This prospective randomized, double-blind, clinical trial was done at the department of obstetrics and gynaecology Patel hospital Karachi, from September 2022 to February 2023. All the adult female patients aged 18 years or older undergoing elective gynecological laparoscopic surgery and willing to receive RSB as a postoperative analgesic technique were included. After taking informed consent, the patients were randomly allocated into two groups. In group I, BRSB was performed with 25 mg of bupivacaine and in group II was given 25 mg of bupivacaine intraperitoneal. Postoperative pain was assessed by visual analog pain score (VAS) at 1st, 6th, 10the and 24the hours postoperatively. All the information was collected via study proformas. Results: The study comprises 60 patients who underwent gynecological laparoscopic surgeries, with group I having a mean age of 38.10+11.19 years and an average BMI of 27.07+5.15 kg/m2, and group II having a mean age of 41.36+11.18 years and an average BMI of 27.51+4.22 kg/m2. Average (VAS) was significantly lower in group I compared to group II at 1st, 6th, 10th, and 24th hour, with a statistically significant p-value of 0.001. The average duration of surgery was not statistically significant in both groups, as an average duration in group I was 32.14+12.20 minutes and in group II was 31.0+19.21 minutes. Conclusion: The use of bupivacaine in a bilateral rectus sheath block (BRSB) with was observed to be more effective for post-laparoscopic pain relief compared to 25 mg of bupivacaine intraperitoneal administration.